The Theory of Coalition Presidentialism: Lessons for Ukraine - Movchan, U. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article is considered the concept of «coalition presidentialism». It has been considered the features in building coalition in parliamentary and presidential systems. Among the indicators of coalition building in parliamentary system are investiture rule, the formateur party, motives of politicians, agreement on the coalition formation, and political fragmentation. In presidential system, they are cabinet appointments, pork, and patronage.